People with diverse needs at the university: support and accessibility on the example of the Maria Grzegorzewska Special Education University in Warsaw - Lejzerowicz, Magda (Niepełnosprawność i praca: Wymiary, konteksty, perspektywy, 2024)
Education of students with diverse needs, including disabilities, poses a challenge for the contemporary higher education system, both for educators adjusting the teaching process and for administrative staff. It brings about many new solutions and educational opportunities for students with disabilities, as well as requiring a certain kind of individualized approach and inclusive design of the teaching process.The aim of the research is to determine the relationship between participation in training and the enhancement of competencies of academic and administrative staff in an inclusive approach, as well as to understand the needs of participants in the university education process. The research problem was formulated as follows: what competencies can be improved and developed during training. Exploring the research problem requires adopting the methodological perspective of participatory action research (Lewin, 2010; Czerepaniak-Walczak, 2014). The results are based on data analysis from research conducted in 2023 with individuals participating in training on adapting the teaching process and administrative support for students with diverse needs at the Maria Grzegorzewska Special Education University in Warsaw. The analysis also took into account the results of research on the needs of students and the experiences of training facilitators.The results of the analysis showed an increase in competencies in inclusive design after participation in training, sensitivity to one’s own and others’ needs, and understanding and empathy towards individuals with diverse needs.The conclusions drawn from the analysis indicate that through training for university staff, it is possible to better design support at the higher education level, adapt materials and forms of communication to the diverse needs of students, especially those with individual educational needs. Therefore, it is crucial to continuously conduct training aimed at improving social, communication, and teaching competencies for university staff, which indirectly affects the level of preparation for future teaching professionals.